The Influence of Language and Culture Learning on Students' Perception of Social Issues in South Korea: Insights from Indonesian Learners of Korean - Ummul Hasanah; Fatmawati Djafri; Nur Endah Nugraheni (Centre for Asian Social Science Research (CASSR), Faculty of Social and Political Sciences, UIN Sunan Gunung Djati Bandung, 2025)
This study explores the influence of learning the Korean language and culture on students’ perceptions of social issues in South Korea. Drawing on the theory of cultural relativism in language acquisition and intercultural understanding, this quantitative research employed an online survey administered to 28 students enrolled in Korean language courses at Gadjah Mada University, Yogyakarta, Indonesia. The participants came from diverse academic backgrounds and demonstrated varying levels of Korean proficiency. Data were analysed using T-tests and linear regression, with interpretation supported by relevant literature. The results indicate a significant positive correlation: students with higher proficiency in Korean language and culture exhibited greater awareness and understanding of South Korean social issues. This suggests that language and cultural education can enhance international awareness and empathy. Despite offering valuable insights, the study has certain limitations, including potential self-reporting bias and its general focus on broad social issues rather than specific topics such as workplace dynamics. Nonetheless, the findings are relevant for language educators, policymakers, and students seeking to deepen their cross-cultural competence.